Familial aggregation of Diabetes: a study based on Patients and Controls in Pune - Sharmistha Aich Srivastava (Asian Pacific Journal of Health Sciences, 2014)
Type 2 Diabetes prematurely kill two-thirds of people in industrialized nations. Large numbers of diabetics in Indian sub continent and their ever-growing numbers are because of rapidly changing lifestyles compounded with inherent susceptibility of Indians to the disease. The study therefore aimed to undertake an anthropological investigation of ‘familial clustering of diabetes’ among Indian population with its possible linear transmission from one generation to other. A study of 1150 subjects was carried that included 750 patients, 400 nested case controls. Diagnosis of disease was based on ‘WHO criteria. Data was collected from various hospitals from Pune such as K.E.M, AFMC, Sassoon Hospital, Poona Hospital, Nandadeep Hospital. Structured questionnaires, in-depth interviews were used. Family History Index (FHI) was calculated. Conventional statistical methods like Yates correction, Odds Ratio (OR), 95 % CI were used. Analysis showed that more than half of diabetic patients had positive family histories. Family History Index (FHI) showed a strong exposure to diabetes with presence of significant familial clustering of diabetes among first degree relatives. The prevalence of diabetes was relatively high among one or both parents, siblings of patients. Thus, it was observed that parents and siblings were the maximum sufferers of diabetes along with strong paternal inheritance. The study reflected the fact that linear transmission of diabetes was strongest among first degree relatives followed by second degree relatives of patients. This implies the fact of presence of strong genetic component in the etiology of the disease which becomes more severe, with various lifestyle factors.